Theoretical justification of the choice of the speed mode during the driving test express diagnostics of transmission units - K. Y. Leliovsky (Интеллект. Инновации. Инвестиции, 2023)
The relevance of the study is determined by the need to solve the problem of operational management of the current technical condition of the rolling stock. Based on this, technical diagnostics activities become important because they allow you to quickly identify the current technical condition of the vehicle in question. At the same time, it is important, even at the stage of planning diagnostic measures, to choose such operational modes of movement along the test section that would ensure the best information content of the test runs. The theoretical substantiation of the choice of speed modes of arrivals of the studied vehicles along the test section of the road during express diagnostics was the purpose of this work. Research methods: analytical mechanics, differential methods, matrix calculus methods, mathematical numerical methods. The main results are in the proposal of a dynamic model of the vehicle transmission, which takes into account the disturbing effects from the engine and from the support base of the test section, where diagnostic runs are carried out. The amplitude-frequency characteristics of vibration accelerations of the vehicle body are calculated when it moves at given speeds along the simulated test diagnostic section. The practical significance of the study is confirmed by the results of the analysis of the obtained graphs, during which a conclusion was made about the most vibration-dangerous frequency ranges. This is important, since vibrations that occur at certain frequencies, which are directly dependent on the speed of movement, as a rule, cause the most intense responses in specific components and parts of transmission units. Further research is related to the theoretical substantiation of the choice of rational ranges of speed modes of the studied vehicles on the test diagnostic section of the support base, taking into account the characteristics and features of its surfaces. The results of the work are aimed at improving the system of maintenance and repair of the rolling stock of motor vehicles, namely, its diagnosis to determine the presence and degree of development of operational defects and damage, as well as the current technical condition of the transmission units.